Inhibition of tumor growth by U0126 is associated with induction of interferon‐γ production. Issue 4 (28th June 2014) - Ma, Xingzhe; Wang, Qixue; Liu, Ying; Chen, Yuanli; Zhang, Ling; Jiang, Meixiu; Li, Xiaoju; Xiang, Rong; Miao, Robert Q.; Duan, Yajun; Han, Jihong
<x xml:space="preserve">Abstract</x> Several MEK1/2 inhibitors have been in clinical trial evaluation for cancer treatment. Interferon‐γ (IFN‐γ) is a cytokine with multiple biological functions including antitumor activity. Expression of IFN‐γ can be induced by liver X receptor (LXR), a ligand‐activated transcription factor. However, it remains unknown if the anti‐cancer action of MEK1/2 inhibitors is completed, at least in part, by activating IFN‐γ expression. In this study, we determined that U0126, a MEK1/2 inhibitor, increased tumor‐free and survival rates and decreased growth of inoculated Lewis lung carcinomas in wild type mice. However, the protective effects were substantially attenuated in IFN‐γ deficient (IFN‐γ−/−) mice. At cellular and molecular levels, MEK1/2 inhibitors increased IFN‐γ protein and mRNA expression and activated natural IFN‐γ promoter but not the IFN‐γ promoters with mutations of the LXR responsive elements (LXREs). MEK1/2 inhibitors also enhanced formation of the LXRE‐nuclear protein complexes by inducing LXR expression and nuclear translocation. Similarly, MEK1/2 siRNA inhibited phosphorylation of ERK1/2 by MEK1/2 while activated IFN‐γ expression. In contrast, inhibition of LXR expression by siRNA blocked MEK1/2 inhibitors‐induced IFN‐γ expression. U0126 also inhibited chemicals‐induced pulmonary carcinomas, which was associated with increased IFN‐γ expression in the lung. Taken together, our study suggests that MEK1/2 inhibitors induce IFN‐γ production in an LXR‐dependent manner and the induction of IFN‐γ expression can partially contribute to the anti‐tumorigenic properties of U0126.